Comparison of the Transparency of Fact-checking: A Global Perspective - Ye, Qiong (Journalism practice, 2023)
In recent years, with the global proliferation of fake news, fact-checking has emerged globally, and transparency has become the consensus of global fact-checkers. Based on the three transparency commitments signed by fact-checkers and IFCN, this article compares the transparency of source, funds, and methodology of fact-checking news in six countries (the United States, the United Kingdom, India, South Africa, Brazil, and Australia) on six continents. The study found that South Africa and the United States are more transparent than other countries. Moreover, transparency is not only related to the social environment, but also related to the subject of verification and the news writing habits of each country. This article also compares the fact-checkers of the NGO model with the newsroom model and finds that the transparency of the fact-checkers of the NGO model is much higher than that of the newsroom model. Through these, this article broadens the perspective of global comparison of fact-checking, and explores the more complicated reasons behind the differences in the transparency of fact-checking across countries.